How does the Loosening Policy of Stock Index Futures Affect the Asymmetric Effect of Futures and Spot Markets - Liu, Jiashu (Transactions on Economics, Business and Management Research, 2024)
By constructing EGARCH (1,1) model, this paper uses the logarithmic returns of CSI 300, SSE 50 and CSI 500 stock index futures in the capital market from 2016 to 2023 to study the leverage effect of each loosening policy on the futures and spot markets. The study found that after the futures market experienced the restriction policy in 2015, the three loosening policies did not cause the market to form an asymmetric effect, and the promulgation of the fourth and fifth loosening policies successfully restored the leverage effect of the market. The reason may be that the first three loosening policies have a short time span and low intensity, and fail to effectively schedule investor sentiment to increase futures trading volume. At the same time, through the Granger causality test, it is found that the information transmission function of the Shanghai and Shenzhen 300 stock index futures market has not been effectively 'repaired'.